Penggunaan Aplikasi Google Classroom untuk Meningkatkan Persepsi Pembelajaran Digital Mahasiswa - Ashif Ardhana, Ivan (Jurnal Riset Pendidikan Kimia (JRPK), 2020)
This purpose of this study is to improve students digital learning perception using Google Classroom in learning chemistry on Physical Chemistry and Basic Analytical Chemistry courses. The subjects were 51 students of fourth semester at Chemistry Education Departement IAIN Tulungagung selected by purposive sampling. Research conducted by the importance of digital learning that slightly experiencing by mostly rural areas students on previously grade school. The method used in this study was one-group only pretest-postest. Hypothesis test uses ttest done by SPSS 21 application for windows. Result shows there was improvement of students’ digital learning perception taught by Google Classroom application. The result includes: (1) there was improvement of students’ perception through Paperless Education concept; (2) there was improvement of students’ perception through Green Chemistry vision; (3) there was improvement of students’ perception through Individual Digital Literation; and (4) here was improvement of students’ perception through Learning Environment Stimulus. This research may helps stakeholder of education institution to use Google Classroom as supporting tools of learning in digital era. <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;"> Keywords Google Classroom, Digital Literation, Paperless Education, Green Chemistry, Learning Environment Stimulus <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">